The riddle of redstone ruins - Collins, Pat; Lynch, Chris (Horwitz Martin Education ; Distributed in United States of America by Richard C. Owen Publishers St. Leonards, Australia, Katonah, N.Y., 2000)
"After accidentally finding the first of many ancient clues, a group of children race to work out a thousand-year-old puzzle. But there are some hidden traps - and the children must take care to read the clues very carefully!"